Antioxidant, phytochemical, and proximate test in cookies fortified with Polyscias scutellaria leaves on development snack for breastfeeding mother - Budiono, Budiono; Pertami, Sumirah Budi; Kasiati, Kasiati; Herawati, Tutik (Journal of Food Technology Research, 2025)
Hypogalactia is a condition characterized by low milk production. Polyscias scutellaria has been traditionally used to increase breast milk production among breastfeeding mothers in East Java, Indonesia. This study aimed to evaluate the antioxidant activity, phytochemical content, and proximate composition of cookies fortified with P. scutellaria leaves. The cookies were divided into three types: regular cookies (RC), which contain gluten and egg; gluten-free cookies (GFC); and gluten-free, egg-free cookies (GFEFC). The antioxidant activity was measured using the 1-diphenyl-2-picrylhydrazyl (DPPH) assay, while phytochemical contents were evaluated by total phenolic content (TPC) and total flavonoid content (TFC). The proximate analysis included total ash, moisture, fat, protein, carbohydrate, and starch content. The antioxidant activity results showed that RC, GFC, and GFEFC reached inhibition activity for DPPH assay of 52.17%, 67.93%, and 64.70%, respectively. GFC had the highest TPC, while GFEFC had the highest TFC. The RC cookies had the highest carbohydrate and protein content, while the highest fat content was found in GFEFC. Proper nutrition is essential for breastfeeding mothers and infants to ensure adequate nutrition for the infant and energy for the mother. In conclusion, cookies fortified with P. scutellaria can be used as a snack for breastfeeding mothers.